2020
DOI: 10.32677/ejms.2020.v05.i03.002
|View full text |Cite
|
Sign up to set email alerts
|

Malaria: Prevalence and related factors in children at Aba, Southeast Nigeria

Abstract: Background: Childhood malaria has remained a major public health burden. It severely affects children aged under-5 years, particularly in Sub-Saharan Africa. Curbing the prevalence of malaria begins with determining the prevalence and related factors of the disease in the community. Objective: The objective of the study was to determine the prevalence and related factors of malaria in children at Aba, Southeast Nigeria. Materials and Methods: In this retrospective study, 275 case files of children admitted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…exclusive breastfeeding has historically been an important predictor for jaundice, the mechanism behind the association is not well understood [16]. This result is in agreement with a study from Nigeria which had shown that (90.4%) of the jaundiced neonates were exclusively breastfed [5]. What it is in breast milk that causes excessive jaundice is not known but unsaturated fatty acids or a lipase which inhibits glucuronyl transferase have been suspected [17].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…exclusive breastfeeding has historically been an important predictor for jaundice, the mechanism behind the association is not well understood [16]. This result is in agreement with a study from Nigeria which had shown that (90.4%) of the jaundiced neonates were exclusively breastfed [5]. What it is in breast milk that causes excessive jaundice is not known but unsaturated fatty acids or a lipase which inhibits glucuronyl transferase have been suspected [17].…”
Section: Discussionsupporting
confidence: 74%
“…In this study the sample size was (160), a study from Nigeria was also resulted in the same sample size (N=160) [5]. In our study, the most common etiological factor for neonatal jaundice was undetermined (51.9%).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The average annual infection rate recorded the lowest infection rate in 2018 (44.4%) which was lower than the 47.1% reported in Jigawa State [12] but higher than the 20.5% reported in North Ethiopia [13]. However, the infection rate in 2017 was higher than 21% reported in South Ethiopia [14]. In 2020, the overall infection rate was lower than 85.1% reported in Aba, Abia State [15].…”
Section: Discussionmentioning
confidence: 92%
“…This part of the study findings indicating most mothers have taken the decision themselves to send the sick babies to the hospital without the husband's approval showed most societies are more concerned about women's empowerment in health decision-making now than previously when most healthcare decisions were often reported to have been taken by the husband. However, results still showed that some of the mother's decision to seek healthcare services for the baby was either taken by the mother-in-law or the husband, and this sometimes led to a delay in health decision-making [36][37][38][39][40][41][42][43]. This still calls for more advocacy to educate and empower women to make major healthcare decisions to help ensure the immediate administration of healthcare interventions to save lives.…”
Section: Sources Of Information About Nnj Among Puerperal Mothersmentioning
confidence: 99%